Sustainable design awareness in Malaysian graphic design scene - Wong, Pow Chin (Universiti Malaysia Sarawak (UNIMAS), 2010)
The main objective of this research is to increase the students and designers awareness about their role as citizen designers towards sustainability awareness. With proper guidelines and education, they will be able to practice sustainability in their designs and improving their environmental effects on the environment as well as for future generations. To investigate the development of communication design, a research will be emphasizing on turning data into visual information. Therefore, the outcome data of the questionnaires distributed to all respondents will be analyzed and integrated as visual definition used in various printed materials and promotional items in this campaign